Socioemotional Trajectories in Black Boys Between Kindergarten and the Fifth Grade: The Role of Cognitive Skills and Family in Promoting Resiliency. (29th July 2013) - Brown, Jeffrey; Barbarin, Oscar; Scott, Kristin
Abstract : Relatively little attention has been paid to emotional functioning of Black boys in contrast to the attention paid to externalizing problems, even though internalizing problems are strong predictors of later well‐being. This study tests a multilevel risk model of emotional well‐being assessing the relation of poverty, maternal functioning, and child cognitive competence to changes in Black boys' internalizing symptoms between kindergarten and the fifth grade. The study utilizes data from the Early Childhood Longitudinal Study–Kindergarten Cohort (ECLS‐K) to describe development of internalizing problems in a nationally representative sample of Black boys ( N  =   1603) over the period. Through Latent Growth Curve Analysis, trajectories were identified that showed some boys with stable levels of internalizing symptoms (high and low levels), and one trajectory showing increases in internalizing problems over time. The model testing confirms that differences in these trajectories can be explained by environmental risks, maternal distress, and boys' cognitive skills. Early cognitive skills proved to be especially valuable in reducing the risk of internalizing problems.